L’opposizione a Darwin di Jakob von Uexküll - RASINI, VALLORI (S&F_scienzaefilosofia.it, 2022)
Jakob von Uexküll’s Opposition to Darwin The Estonian biologist Jakob von Uexküll is considered an important precursor of environmental ecology and a forerunner of zoosemiotics. He was at the centre of German scientific and philosophical debate in the early 20th century for his «theoretical biology» and his theory of «subjective environments». His positions were radically opposed to Darwinian evolutionary theory; however, his arguments often appear flawed by profound misunderstandings, interpretative distortions and confusion between the positions of Darwin's supporters. Added to this is the strong prejudice against a revolutionary worldview regarded as a new religion.